Authorship Order in Medical Education Publications: In Search of Practical Guidance for the Community. Issue 3 (27th May 2019) - Mavis, Brian; Durning, Steven J.; Uijtdehaage, Sebastian
Abstract: Phenomenon: With scholarly collaborations come questions about the order of authorship. Authorship order is an important consideration because it often used as an indicator of seniority, expertise, leadership, and scholarly productivity. As a result, authorship order factors into decisions about hiring, salary, resource allocation, and professional advancement. This study describes principles commonly applied to authorship order decisions within the medical education community and educators' opinions about the significance of authorship order. Approach: A questionnaire was developed to ascertain current practices related to authorship decisions. Sixteen items were rated in terms of frequency of actual use and the desirability of the practice using a 4-point rating scale: 1 ( never ), 2 ( sometimes ), 3 ( often ), and 4 ( always ). Additional questions addressed the perceived significance of authorship order. The last set of questions provided information about respondents' personal and career characteristics. The survey was delivered via e-mail to a random sample of 391 subscribers from the DR-ED listserv. Findings : Fifty-four e-mail addresses were returned as undeliverable; of the remaining 337 mailed surveys, 109 responses (32.3%) were received. Five of the current practices for determining authorship order were rated as both frequent and desirable; 4 items had low ratings suggesting that these practices were both infrequent and undesirable. For 7 items, there was a significant gap between the ratings of practice frequency and desirability. When asked about preferred authorship order strategies, most respondents (94%) endorsed listing authors by descending order based on contribution but were split in identifying the last author (47%) or second author (46%) as the next best placement after first author. Respondents supported the practice of many journals requiring authors to disclose their contributions, agreeing (69%) that it provides useful information for promotion and tenure committees; however, 43% were uncertain about how disclosed contributions were reflected in authorship order. Insights : Respondents strongly endorsed the importance of listing authors in order of decreasing contribution, although the meaning of second versus last author lacks consensus. This finding, together the other strategies that received strong endorsement and those that were not strongly endorsed, provides a starting point to develop guidance for medical educators about how to determine authorship order. Clear guidance for authors would promote fairness and accountability within the medical education community as well as provide more consistent interpretation for those who consider authorship order for career- and resource-related decisions.